Preterm Labor and Preterm-PROM at a Lower Gestational Age Are Associated with a Longer Latency-to-Delivery Even in Patients with the Same Intensity of Intra-Amniotic Inflammation: “Carroll-Model” Revisited - Jeong-Won Sohn; Eun-Saem Choi; Chan-Wook Park; Kyung-Chul Moon; Joong-Shin Park; Jong-Kwan Jun (Life, 2022)
A previous study by Carroll et al. demonstrated that the time from preterm-PROM to delivery was longer at a lower gestational age (GA) when the membranes rupture, although the presence or absence of intra-amniotic inflammation (IAI) was not examined in that study. However, patients with either preterm labor (PTL) or preterm-PROM at a lower GA had more frequent IAI, which was associated with a shorter amniocentesis-to-delivery (ATD) interval as compared with inflammation-free amniotic fluid (AF). Up to now, there is no information about whether PTL and preterm-PROM at a lower GA are associated with a shorter or longer latency to delivery in cases with the same intensity of IAI. The objective of the study is to examine this issue. AF MMP-8 was measured in 476 singleton early preterm-gestations (21.5 < GA at amniocentesis < 34 wks) with PTL (n = 253) and preterm-PROM (n = 223). Patients were divided into three groups according to GA at amniocentesis (i.e., group-1: <26 wks; group-2: 26–30 wks; group-3: 30–34 wks). IAI was defined as an elevated AF MMP-8 (≥23 ng/mL), and IAI was classified into either mild IAI (AF MMP-8: 23–350 ng/mL) or severe IAI (AF MMP-8 ≥ 350 ng/mL). ATD interval was examined according to GA at amniocentesis in the context of the same intensity of IAI (i.e., inflammation-free AF, mild IAI, and severe IAI) among pregnant women with either PTL or preterm-PROM. IAI was more frequent at a lower GA in cases with PTL (group-1 vs. group-2 vs. group-3; 59.5% vs. 47.4% vs. 25.1%; X2test, p = 0.000034 and linear by linear association [LBLA], p = 0.000008) and in those with preterm-PROM (group-1 vs. group-2 vs. group-3; 69.2% vs. 50.0% vs. 32.0%; X2test, p = 0.000104, and LBLA, p = 0.000019). Of note, cases without IAI at a lower GA had a longer ATD interval in both PTL (Spearman’s rank correlation test, γ = −0.360, p = 0.000003) and preterm-PROM (γ = −0.570, p = 0.000001) groups. Moreover, the lower the GA, the longer the ATD interval, even among patients with mild and severe IAI in both PTL (Spearman’s rank correlation test; mild IAI, γ = −0.290, p = 0.039; severe IAI, γ = −0.299, p = 0.048) and preterm-PROM (mild IAI, γ = −0.565, p = 0.000013; severe IAI, γ = −0.363, p = 0.015) groups. In conclusion, PTL and preterm-PROM at a lower GA are associated with a longer latency to delivery, even in patients with the same intensity of IAI. This finding suggests that a more intense IAI may be needed for spontaneous preterm birth at a lower GA.